Circular resonator based two ports optical switch - Dikshit A.K.; Tiwari S.; Jit S.; Pandey A.; Pandey P.C. (My University, 2025)
We propose a design of two ports resonator based optical switch. The power of the switch has been enhanced by employing the cavities in 2-D photonic crystal. Also, we obtained the peaks of different wavelength at different output port. © OSA 2014.